Síntese, caracterização e avaliação farmacológica de derivados N-acilhidrazônicos para a prevenção de aterotrombose - Svendsen, Arthur Flohr [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Atherosclerosis is a chronic inflammatory disease characterized by accumulation of lipid and fibrous components in arterial vessels, giving rise to atheromas. Development of Atheromatou plaques leads to arterial steatosis, triggering ischemic events. Atherotrombosis has a strong correlation with atherosclerosis, where rupture of atheromatous plaques cause release of vessel wall's pro-thrombotic components, activating platelet aggregation and thromosis. Due to the major role played by platelets on thrombus-embolic conditions, drugs that inhibit platelet aggregation demonstrate great relevance for atherothrombosis prevention, reducing patient mortality. Currently, there are a variety of drugs acting on several different targets, preventing platelet activation. However, these therapies demosntrate side effects such as thrombocytopenia, neutropenia, hemorrhage and low oral availability. Thus, the application of molecular modifications such as hybridization can produce novel, more efficient antiplatelet aggregation inhibitors. In this project we describe the synthesis and characterization of novel N-acilhydrazone compounds, acting through multiple mechanisms such as platelet calcium chelation and nitric oxide donation by furoxanic subunits. Furthermore, we demonstrate that such compounds exhibit biological activity in in vivo bleeding time, in vitro antiplatelet aggregation and in vivo antinociceptive assays. Therefore, novel N-acilhydrazone compounds demonstrate potential as antiplatelet drugs for atherothrombosis prevention.

A aterosclerose é uma doença inflamatória de caráter crônico caracterizada pelo acúmulo de lipídio e componentes fibrosos em artérias, formando ateromas. O desenvolvimento de placas ateromatosas causa estenose arterial, causando eventos isquêmicos. A aterotrombose tem intima associação com a aterosclerose, pois a ruptura da placas ateroscleróticas gera extravasamento de conteúdo pró-trombótico dos vasos, levando a ativação da agregação plaquetária e consequente geração de trombos. Devido à atividade essencial das plaquetas nos processos das doenças tromboembólicas, os fármacos que inibem a agregação plaquetária possuem valor na prevenção da aterotrombose, reduzindo a mortalidade de pacientes. Atualmente existem diversos fármacos que atuam na prevenção da ativação plaquetária em diversos alvos terapêuticos. Entretanto, tais terapias farmacológicas apresentam diversos efeitos adversos como trombocitopenia, neutropenia, hemorragia e baixa disponibilidade oral. Assim, a utilização de ferramentas de modificação molecular, como a hibridação, para obter novos fármacos antiagregantes plaquetários mais efetivos se mostra necessária. Neste trabalho demonstramos a síntese e caracterização de derivados N-acilhidrazônicos com múltiplos mecanismos de ação. Também são demonstrados resultados satisfatórios em ensaios pré-clínicos de tempo de sangramento, agregação plaquetária e analgesia. Logo, os compostos N-acilhidrazônicos demonstram-se como bons candidatos a fármacos para a prevenção de aterotrombose.
Keywords: Aterosclerose; Tromboembolismo; Fármacos; Atherosclerosis